Scolex on the Brain: Intraventricular Neurocysticercosis - Olivia Mobarakai; Robert Summey (Annals of Internal Medicine: Clinical Cases)
Neurocysticercosis is a parasitic infection caused by the pork tapeworm Taenia solium. Intraventricular neurocysticercosis develops when cysticerci become lodged in the ventricular outflow tract, which occurs in 10% to 20% of cases. Identification of a scolex within a cystic lesion is pathognomonic. Neurosurgical consultation is recommended to determine the appropriate operative course. When possible, removal of cysticerci using an endoscopic approach is recommended. We present a case of a 22-year-old woman from Honduras who was found to have obstructive hydrocephalus secondary to intraventricular neurocysticercosis and was treated successfully with shunt placement followed by medical therapy.